STUDY OF HELMINTHIASIS IN ELEMENTARY SCHOOL CHILDREN IN JAMBI CITY - Maria, Ima; Aurora, Wahyu Indah Dewi; Darmawan, Armaidi; Kusdiyah, Erny; Nuriyah, Nuriyah (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
ABSTRACTIntroduction: Intestinal parasitic infection is a major health problem in developing countries,especially in children, which often causes mortality and morbidity. Worms affect one third of theworld's population. School-age children between the ages of 5 and 15 years in most developingcountries are at the highest risk of chronic helminthic infection and worm-related morbidity. This studyaims to determine the prevalence and determinants of helminthiasis in school-age children.Methods: This research is a quantitative study with a cross-sectional design. The research will beconducted at Jambi City Elementary School in August-October 2022. The total sample is 369respondents using a simple random sampling technique.Results: The type of worm eggs found were Ascaris lumbricoides worm eggs. The most gender ismale (50.7%), the most sources of water for cooking and drinking at home are Refill Water (28.2%),the habit of washing vegetables and raw meat with running water is 90.8%, the number of childrenplaying outside the house the most 76.2%, playing sand 75.9%, using sandals 94.5%, habit of bitingnails 9.8%, washing hands after playing 85.6%, consuming worm medicine 53.1%, and still there arehouses that have floors in the form of land as much as 3.3%.Conclusion: The risk factor for helminthiasis in the community is still high. Only some childrenconsume deworming drugs regularly at their own expense. Government intervention is needed inmass deworming treatment for school childrenKeywords: Worms, Elementary School Children